(untitled) (Conference Zone, 2022)
In this article, the task is to consider effective modern pedagogical technologies that a teacher of the Russian language and literature can apply in his work. Particular attention is paid to the technologies of the activity method, which form in students the ability to independently obtain new knowledge, collect the necessary information, put forward hypotheses, draw conclusions and conclusions, not get lost in a situation of uncertainty, be able to establish effective communications with different people, remain moral.